Prevalence, Risk Factors and Predictors of Adverse Outcomes of Febrile Neutropenia in Oncology Patients on Chemotherapy at the Red Cross War Memorial Children's Hospital: A Three Year Retrospective Study - Adekunle, Motunrayo (Department of Paediatrics and Child Health, 2022)
Background: Febrile neutropenia (FN) is the commonest fatal acute complication of cancer treatment in children. The need for regional clinical decision rules allowing for home-based care in those at low risk for adverse outcomes has been identified. Aims: To evaluate the prevalence and potential risk factors for FN, identify adverse outcomes and validate a tool to identify risk for adverse outcomes in a cohort of children treated for cancer at the Red Cross War Memorial Children's Hospital, Cape-Town, South Africa. Methodology: A retrospective cohort study from 1st January 2017 to 31st December 2019. Results: In all, 179 patients had chemotherapy and 267 FN episodes occurred. Independent predictors of FN were AML (p = 0.039), ALL (p = 0.020) and intensive chemotherapy (p = < 0.001). Mucositis (p = 0.001), CVAD (p = 0.004, haematologic malignancies (p = 0.040), blood transfusion during FN episode (p = 0.001) and severe neutropenia (white cell counts< 0.3 x 109 cells/L) (p = < 0.001) were risk factors for adverse outcomes. The mortality rate from FN was 3.57%. Independent predictors of adverse outcomes were AML (p = 0.001), CVAD in-situ (p = 0.019) and severe neutropenia (p = 0.005). Validation of risk stratification for adverse outcomes using the Swiss Paediatric Oncology Group (SPOG) index with a cut-off value of nine demonstrated a sensitivity and specificity of 52.3% and 62.0%, respectively. Positive and negative predictive values were 56.3% and 58.2%, respectively, with an overall accuracy of 57.4%. In our cohort, coordinates of the curve are best able to predict adverse outcomes with a cut-off value of 7.5. Conclusion: Adverse outcomes from treatment are likely in children with AML, severe neutropenia and those with CVADs in-situ. A lower cut-off of 7.5 using the SPOG FN risk index best predicted adverse outcomes in our cohort.